ANALISIS KEARIFAN LOKAL PENGELOLAAN LUBUK LARANGAN SUNGAI KAITI UNTUK PENGEMBANGAN MODUL KONSEP PELESTARIAN LINGKUNGAN DI SMA - Hasibuan, Untung Hasibuan; Fauziah, Yuslim Fauziah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The research was conducted to determine Sialang Jaya Local Wisdom Society in Kaiti river management in December 2014 until February 2015. The research used for the development of the module unit concept of Environmental Conservation Biology learning in Senior High School, in two stages namely stage of Research and Development stage unit module. Collecting data with interviews method with snowball sampling technique with key informants that the Governing Lubuk Larangan, Irish Indigenous Community Leaders. Additionally used methods of observation and documentation techniques. The results showed that the Community Sialang Jaya has a variety of Local Wisdom in managing the river, among others, (1) Planning, Sialang Jaya Society has Local Knowledge (Spatial land use is residential, Lubuk Larangan and plantations and the determination of the Lubuk Larangan); (2) Utilization, utilize Society to preserve resources for taking fish is prohibited except on designated days and vegetation watersheds.); (3) Control, existence of deterrence, prevention, and recovery through abstinence prohibited.); (4) Maintenance, existence of prevention and preservation through mutual cooperation Mandurung and Horja to keep the preservation of the river by using Etnoteknologi and believe in the myth.); (5) Supervision, board structure and functions of traditional leaders); (6) Law Enforcement, existence of sanctions for offenders sanctions of society. The results could be used as a unit of learning modules on the concept of Environmental Conservation Biology in Senior High School. Keywords: Local Wisdom, Snowball Sampling, Lubuk Larangan, Module.